Pengembangan Media Pembelajaran Berbasis Animaker dengan Pendekatan Deep Learning - Aqidatun Nisa'; Machnunah Ani Zulfah; Moh. Fodhil (Lembaga Yasin AlSys, 2026)
Although the importance of interactive learning media has received attention in various studies, research that specifically discusses the development of Animaker-based media with a Deep Learning approach on the history of Walisongo remains limited. This study aims to develop and determine the effectiveness of Animaker-based learning media with a Deep Learning approach on the topic of emulating the role of Walisongo in spreading Islam. This study used a quantitative approach with a Research and Development (R&D) design based on the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 36 students of Class X-6 at SMA PGRI 1 Jombang selected through random sampling. Data were collected using media expert and material expert validation questionnaires, student response questionnaires, and learning outcome tests in the form of pre-tests and post-tests. Data were analyzed using Likert-scale percentage techniques and the N-Gain formula. The results show that the level of media validity reached 92–96%, with a highly feasible category, student responses were in the very positive category, and media effectiveness based on the N-Gain calculation reached 70%, with a moderately effective category. This finding contributes to the development of digital learning media theory and broadens understanding of the implementation of Deep Learning in the context of Islamic Religious Education. The conclusion of this study emphasizes that animation-based learning media innovation plays an important role in improving students’ understanding of Islamic history material. The practical implications of this study indicate that teachers and schools can integrate Animaker-based media to create Islamic Religious Education learning that is more interactive, meaningful, and aligned with students’ learning needs.